Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fpsyg.2021.820045
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Personality in Prediction of Satisfaction With Life in Recreational Athletes During the First Wave of Pandemic Covid-19

Abstract: The aim of this research is to contribute to the understanding of the concept of satisfaction with life by determining the relationship between personality traits and the subjective experience of satisfaction with life in students—recreational athletes. This research is based on the biological theory of personality by Hans Eysenck and it attempts to offer explanations of a possible change in satisfaction with life in the period of great social deprivation caused by the Covid-19 pandemic. The sample of subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Ultimately, we reduced the 79 terms for professional personality traits to 45 terms for the formal application of the SCCPPT. [39]. For example, Allport's (1931) theory of personality traits pioneered the study thereof by using terms or lexical words [40].…”
Section: Methodsmentioning
confidence: 99%
“…Ultimately, we reduced the 79 terms for professional personality traits to 45 terms for the formal application of the SCCPPT. [39]. For example, Allport's (1931) theory of personality traits pioneered the study thereof by using terms or lexical words [40].…”
Section: Methodsmentioning
confidence: 99%
“…A series of studies indicate that many factors could affect the self-assessment of life satisfaction in young people [47]. Several variables, including socio-demographic features (age, gender, educational level, and marital status), health, and income, had a negligible role in explaining the variance in satisfaction with life [48]. Personality traits might affect medical students' psychological adaptation to the real world, and their life satisfaction [48].…”
Section: Life Satisfactionmentioning
confidence: 99%
“…Several variables, including socio-demographic features (age, gender, educational level, and marital status), health, and income, had a negligible role in explaining the variance in satisfaction with life [48]. Personality traits might affect medical students' psychological adaptation to the real world, and their life satisfaction [48]. Another study has revealed that personality traits are significantly associated with variance in satisfaction with life in young people [49].…”
Section: Life Satisfactionmentioning
confidence: 99%